Exploring Plasmodium falciparum Var Gene Expression to Assess Host Selection Pressure on Parasites During Infancy - Kivisi, Cheryl A.; Muthui, Michelle; Hunt, Martin; Fegan, Greg; Otto, Thomas Dan; Githinji, George; Warimwe, George M.; Rance, Richard; Marsh, Kevin; Bull, Peter C.; Abdi, Abdirahman I. (Frontiers in Immunology, 2019)
In sub-Saharan Africa, children below five years bear the greatest burden of severe malaria because they lack naturally acquired immunity that develops following repeated exposure to infection by Plasmodium falciparum. Antibodies to the surface of P. falciparum infected erythrocytes (IEs) play an important role in this immunity. In children under the age of six months, relative protection from severe malaria is observed and this is thought to be partly due to trans-placental acquired protective maternal antibodies. However, the protective effect of maternal antibodies has not been fully established especially the role of antibodies to variant surface antigens (VSA) expressed on IE. Here, we assessed the immune pressure on parasites infecting infants using markers associated with the acquisition of naturally acquired immunity to surface antigens. We hypothesised that, if maternal antibodies to VSA imposed a selection pressure on parasites, then the expression of a relatively conserved subset of var genes called group A var genes in infants should change with waning maternal antibodies. To test this, we compared their expression in parasites from children between 0-12 months and above 12 months of age. The transcript quantity and the proportional expression of group A var subgroup, including those containing domain cassette 13 were positively associated with age during the first year of life, which contrasts with above 12 months. This was accompanied by a decline in infected erythrocyte surface antibodies and an increase in parasitema during this period. The observed increase in group A var gene expression with age in the first year of life when the maternal antibodies are waning and before acquisition of natural acquired antibodies with repeated exposure is consistent with the idea that maternally acquired antibodies impose a selection pressure on parasites that infect infants and may play a role in protecting these infants against severe malaria.